The Power of Metaphor: Examining Its Influence on Social Life. 2014
DOI: 10.1037/14278-007
|View full text |Cite
|
Sign up to set email alerts
|

Toward a metaphor-enriched personality psychology.

Abstract: Conventional wisdom on metaphor suggests that it is the province of poets, metaphor is an optional way of thinking, or that metaphor merely serves communication purposes. In this chapter, we show that such wisdom is at variance with how human beings actually think and function. We first provide a brief overview of the metaphor representation perspective. We then make a case for the utility of this perspective in understanding how people differ from each other and do so within a broader context of how personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 68 publications
(88 reference statements)
1
17
0
Order By: Relevance
“…Since then, a body of social cognitive work has shown that perceptual manipulations consistent with prominent metaphors (e.g., “good is up”: Meier & Robinson, 2004a) alter cognition and social judgments in a metaphor-consistent direction (Landau et al, 2010). There are many gaps in our current knowledge, but the primary one from our perspective is that metaphor representation theory has yet to contact the personality literature as much as might be desired (Robinson & Fetterman, in press), aside from a handful of studies examining personality trait predictors of reaction time processes (Meier & Robinson, 2006; Moeller, Robinson, & Zabelina, 2008; Robinson, Zabelina, Ode, & Moeller, 2008; Sherman & Clore, 2009). Yet, if metaphoric processes do constrain thought, feeling, and behavior in the manner suggested by Lakoff and Johnson (1999), the metaphor representation perspective might have largely untapped potential in understanding individual differences.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since then, a body of social cognitive work has shown that perceptual manipulations consistent with prominent metaphors (e.g., “good is up”: Meier & Robinson, 2004a) alter cognition and social judgments in a metaphor-consistent direction (Landau et al, 2010). There are many gaps in our current knowledge, but the primary one from our perspective is that metaphor representation theory has yet to contact the personality literature as much as might be desired (Robinson & Fetterman, in press), aside from a handful of studies examining personality trait predictors of reaction time processes (Meier & Robinson, 2006; Moeller, Robinson, & Zabelina, 2008; Robinson, Zabelina, Ode, & Moeller, 2008; Sherman & Clore, 2009). Yet, if metaphoric processes do constrain thought, feeling, and behavior in the manner suggested by Lakoff and Johnson (1999), the metaphor representation perspective might have largely untapped potential in understanding individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we would expect preferences for the color red over blue to predict anger and aggression (Fetterman, Robinson, Gordon, & Elliot, 2011). Indeed, we regard a metaphoric approach to personality as an especially generative one in answering important questions concerning how and why people differ from each other (Robinson & Fetterman, in press), particularly given the extensive corpus of linguistic metaphors collected and analyzed by metaphor scholars (Gibbs, 1994; Lakoff & Johnson, 1999). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations